Allogeneic stem cell transplantation for patients with acute myeloid leukemia (AML) in second complete remission (CR2) transplanted from unrelated donors with post-transplant cyclophosphamide (PTCy). A study on behalf of the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation - Nagler, Arnon; Labopin, Myriam; Swoboda, Ryszard; Kulagin, Alexander; Labussière-Wallet, Hélène; Rovira, Montserrat; Blaise, Didier; Vydra, Jan; Yakoub-Agha, Ibrahim; Choi, Goda; Reményi, Péter; Koc, Yener; et al. (Bone marrow transplantation, 2023)
Post-transplant cyclophosphamide (PTCy) is being increasingly used as graft-versus-host disease (GVHD) prophylaxis post allogeneic hematopoietic stem cell transplantation (allo-HSCT) in patients with acute myeloid leukemia (AML) transplanted in first complete remission (CR1). However, results may differ in patients transplanted in CR2. We retrospectively evaluated transplant outcomes of adult AML patients transplanted between 2010-2019 from 9-10/10 human leukocyte antigen (HLA)-matched unrelated donor (UD) in CR2. In total, 127 patients were included (median age 45.5 years, 54% male). Median follow-up was 19.2 months. Conditioning was myeloablative (MAC) in 50.4% and the graft source was peripheral blood in 93.7% of the transplants. Incidence of acute (a)GVHD II-IV and III-IV was 26.2% and 9.2%. Two-year total and extensive chronic (c)GVHD were 34.3% and 13.8 %, respectively. Two-year non-relapse mortality (NRM), relapse incidence (RI), leukemia-free survival (LFS), overall survival (OS), and GVHD-free, relapse-free survival (GRFS) were 17.2%, 21.1%, 61.7, %, 65.2%, and 49.3%, respectively. Time from diagnosis to transplant (>18 months) was a favorable prognostic factor for RI, LFS, OS, and GRFS while favorable risk cytogenetics was a positive prognostic factor for OS. The patient's age was a poor prognostic factor for NRM and cGVHD. Finally, the female-to-male combination and reduced intensity conditioning (RIC) were poor and favorable prognostic factors for cGVHD, respectively. We conclude that PTCy is an effective method for GVHD prophylaxis in AML patients undergoing allo-HCT in CR2 from UD.
Keywords: Unrelated Donors; cyklofosfamid; Retrospective Studies; Middle Aged; mužské pohlaví; nemoc štěpu proti hostiteli; Leukemia, Myeloid, Acute; Adult; kostní dřeň; recidiva; Transplantation Conditioning; příprava pacienta k transplantaci; Hematopoietic Stem Cell Transplantation; ženské pohlaví; transplantace hematopoetických kmenových buněk; retrospektivní studie; Humans; Cyclophosphamide; Graft vs Host Disease; Recurrence; Acute Disease; akutní myeloidní leukemie; lidé středního věku; akutní nemoc; dospělí; Bone Marrow; Female; nepříbuzný dárce; lidé; Male